Martin, O. (2003), Sociología de las ciencias, Buenos Aires: Ediciones Nueva Visión, 139 pp. - Romero, Lucia (Redes. Revista de Estudios Sociales de la Ciencia y la Tecnología, 2006)
Reseña del libro: Martin, O. (2003), Sociología de las ciencias, Buenos Aires: Ediciones Nueva Visión, 139 pp.